Evaluating the progress in achieving Good Environmental Status in the Mediterranean: A methodology to assess the effectiveness of Marine Strategy Framework Directive's Programmes of Measures. (February 2022) - Gorjanc, Sašo; Klančnik, Katja; Papadopoulou, Nadia K.; Murillas-Maza, Arantza; Jarni, Klara; Paramana, Theodora; Pavičić, Mišo; Ronchi, Francesca; Uyarra, Maria C.; Koren, Špela; Dassenakis, Manos; Vidjak, Olja; et al.
Abstract: The Marine Strategy Framework Directive (2008/56/EC) aims to achieve Good Environmental Status of the European Union's marine waters for which the EU Member States are preparing Programmes of Measures (PoMs) to coordinate policies and improve the marine environmental status. These Programmes are revised every six years, yet there is currently no comprehensive and robust methodology to assess the effectiveness of PoMs and their contribution to reaching Good Environmental Status. This paper presents a new and concrete methodology combining policy, socio-economical, and environmental aspects, relying on available monitoring data, official reporting, and expert judgement to yield easily comparable numerical results. The utility of this methodology is also demonstrated on a series of hypothethical measures under descriptors 1 (Biological diversity), 3 (Commerical fisheries stocks), 6 (Seafloor integrity), and 10 (Marine litter). The demonstration shows how the method can be used by policy and decision-makers across the EU, as well as a variety of expert and non-governmental actors to evaluate the progress and potential of individual PoMs on national and (sub)regional levels. Therefore, the method could pave the way to more coherent, coordinated and effective measures to protect EU seas. Highlights: A new effectiveness methodology for the MSFD Programme of Measures is presented. The method is demonstrated through four different MSFD Descriptors. Monitoring data, official reporting and expert judgement provide numerical results. The method is a tool for improving coordination and coherence of MSFD measures. Integrating policy & environmental aspects, the method offers a complete evaluation.